How has early marriage, a critical social determinant of child stunting and wasting, changed over a decade in South Asia? trends, inequities and drivers, 2005 to 2018 - Scott, Samuel; Nguyen, Phuong; Neupane, Sumanta; Pramanik, Priyanjana; Nanda, Priya; Menon, Purnima; Bhutta, Zulfiqar; Afsana, Kaosar (Oxford Academic, 2022)
This article was published in Current Developments in Nutrition by Oxford Academic [© Oxford University Press 2020.] and the definite version is available at: https://doi.org/10.1093/cdn/nzaa061_112 The Journal's website is at: https://academic.oup.com/cdn/article/4/Supplement_2/1484/5844147